Evaluating the Quality of a Teacher’s Made Test against Five Principles of Language Assessment - Sumarsono, Dedi; Arrafii, Moh. Arsyad; Imansyah, Imansyah (Journal of Languages and Language Teaching, 2023)
Classroom assessment serves both summative and formative functions to gauge evidence, evaluate and improve student learning. Assessment evidence is only meaningful when it reflects the true picture of student learning. In this sense, the role of effective assessment instrument, such as test, as crucial to obtain a valid and reliable evidence of student learning. However, we remain in caution about the ability of teachers in designing and developing assessment instruments which are underpinned by a sound theoretical understanding of language assessment principles.This research is set out to evaluate classroom-based assessment instrument (e.g., language test) against five principles of language assessment. To achieve the intended purposes, the research adopts an evaluative research approach by which assessment instrument developed by a teacher was evaluated and rated against the principles. Documentation was used as a method to collect data by which language tests developed by teachers were collected in person. The teachers’ made testscollected in this study were analysed deductively based on five principles of language assessment. The study indicates that the teacher-made test was in general meet all aspects ofthe principles. However, some aspects within principles are not adequately addressed. Some principal suggestions are provided.